Sex Dimorphic Responses of the Hypothalamus–Pituitary–Thyroid Axis to Maternal Separation and Palatable Diet - Jaimes-Hoy, Lorraine; Romero, Fidelia; Charli, Jean-Louis; Joseph-Bravo, Patricia (Frontiers in Endocrinology, 2019)
Neonatal stress contributes to the development of obesity and has long-lasting effects on elements of the hypothalamus–pituitary–thyroid (HPT) axis. Given the importance of thyroid hormones in metabolic regulation, we studied the effects of maternal separation and a high-fat/high-carbohydrate diet (HFC), offered from puberty or adulthood, on HPT axis activity of adult male and female Wistar rats. Pups were non-handled (NH) or maternally separated (MS) 3 h/day at postnatal days (Pd) 2–21. In a first experiment, at Pd60, rats had access to chow or an HFC diet (cookies, peanuts, chow) for 1 month. Male and female NH and MS rats that consumed the HFC diet increased their caloric intake, body weight, and serum insulin levels; fat weight increased in all groups except in MS males, and serum leptin concentration increased only in females. Mediobasal hypothalamus (MBH) Pomc expression increased in NH-HFC females and Npy decreased in NH-HFC males. MS males showed insulinemia and hypercortisolemia that was attenuated by the HFC diet. The HPT axis activity response to an HFC diet was sex-specific; expression of MBH thyrotropin-releasing hormone-degrading ectoenzyme (Trhde) increased in NH and MS males; serum TSH concentration decreased in NH males, and T4 increased in NH females. In a second experiment, rats were fed chow or an HFC diet from Pd30 or 60 until Pd160 and exposed to 1 h restraint before sacrifice. Regardless of neonatal stress, age of diet exposition, or sex, the HFC diet increased body and fat weight and serum leptin concentration; it induced insulinemia in males, but in females only in Pd30 rats. The HFC diet's capacity to curtail the hypothalamus–pituitary–adrenal axis response to restraint was impaired in MS males. In restrained rats, expression of Trh in the paraventricular nucleus of the hypothalamus, Dio2 and Trhde in MBH, and serum thyroid hormone concentration were altered differently depending on sex, age of diet exposition, and neonatal stress. In conclusion, metabolic alterations associated to an HFC-diet-induced obesity are affected by sex or time of exposition, while various parameters of the HPT axis activity are additionally altered by MS, pointing to the complex interplay that these developmental influences exert on HPT axis activity in adult rats.